Video Animasi Interaktif 3d Dampak Penggunaan Gadget Pada Anak Sekolah Dasar Tingkat Awal - Chatleen Prisilia Ompi; Sherwin R.U.A. Sompie; Brave A. Sugiarso (Universitas Sam Ratulangi, 2020)
The presence of gadgets that has offered millions of convenience for sure Â is very much loved by children, not spared are the early children of age. At their age when it is very easy to absorb and imitate, gadget addiction will greatly affect the stimulation of their intelligence development. By utilizing the development of the animation industry which should not be merely for entertainment but rather for education, this research aims to create an Interactive Animation Video based on 3 Dimensions Impact of gadget usage. In this research, MDLC (Multimedia Development Life Cycle) method is used. Based on the results of user evaluations conducted online, many respondents found it helpful to have an interactive video animation. This interactive application is also considered interesting so it is suitable to be applied as an educational medium.